Two-year outcomes of the ranibizumab for edema of the mAcula in diabetes (READ-2) study - Nguyen, Quan Dong; Shah, Syed Mahmood; Khwaja, Afsheen A; Channa, Roomasa; Hatef, Elham; Do, Diana V; Boyer, David; Heier, Jeffery S; Abraham, Prema; Thach, Allen B; Lit, Eugene S; Foster, Bradley S; et al. (Ophthalmology (Rochester, Minn.), 2010)
To determine the long-term effects of ranibizumab (RBZ) in patients with diabetic macular edema (DME). Prospective, randomized, interventional, multicenter clinical trial. One hundred twenty-six patients with DME. Subjects were randomized 1:1:1 to receive 0.5 mg RBZ at baseline and months 1, 3, and 5 (group 1), focal or grid laser photocoagulation at baseline and month 3 if needed (group 2), or a combination of 0.5 mg RBZ and focal or grid laser at baseline and month 3 (group 3). Starting at month 6, if retreatment criteria were met, all subjects could be treated with RBZ. The mean change from baseline in best-corrected visual acuity (BCVA) at month 24. After the primary end point at month 6, most patients in all groups were treated only with RBZ, and the mean number of injections was 5.3, 4.4, and 2.9 during the 18-month follow-up period in groups 1, 2, and 3, respectively. For the 33 patients in group 1, 34 patients in group 2, and 34 patients in group 3 who remained in the study through 24 months, the mean improvement in BCVA was 7.4, 0.5, and 3.8 letters at the 6-month primary end point, compared with 7.7, 5.1, and 6.8 letters at month 24, and the percentage of patients who gained 3 lines or more of BCVA was 21, 0, and 6 at month 6, compared with 24, 18, and 26 at month 24. The percentage of patients with 20/40 or better Snellen equivalent at month 24 was 45% in group 1, 44% in group 2, and 35% in group 3. Mean foveal thickness (FTH), defined as center subfield thickness, at month 24 was 340 μm, 286 μm, and 258 μm for groups 1, 2, and 3, respectively, and the percentage of patients with center subfield thickness of 250 μm or less was 36%, 47%, and 68%, respectively. Intraocular injections of RBZ provided benefit for patients with DME for at least 2 years, and when combined with focal or grid laser treatments, the amount of residual edema was reduced, as were the frequency of injections needed to control edema. Proprietary or commercial disclosure may be found after the references.